Hubungan Pengetahuan Ibu Terhadap Perawatan Tali Pusat Pada Bayi Baru Lahir di PMB Indah Sari Desa Naga Timbul Tanjung Morawa Kabupaten Deli Serdang Tahun 2023 - Syafitri Syafitri; Erin Padilla Siregar (Calory Journal Medical Laboratory Journal, 2023)
Umbilical cord infections occur around 23-91% because the umbilical cord is not cared for properly and there is even a risk of being infected with the bacillus Clostridium tetani bacteria in the first 72 hours after birth. This is greatly influenced by the mother's knowledge in providing correct umbilical cord care. The general aim of this research is to determine whether there is a relationship between maternal knowledge and umbilical cord care for newborn babies at PMB Indah Sari Tanjung Morawa, Deli Serdang Regency in 2023. Umbilical cord care is the treatment and tying of the umbilical cord which causes the final physical separation between mother and baby, then The umbilical cord is maintained in a sterile, clean, dry, vaginal condition and avoids umbilical cord infections (Hidayat, 2015). Good umbilical cord care is one effort to prevent neonatal infections. This research uses quantitative research using retrospective research. The design of this research was carried out using a cross sectional approach, the sample was 35 newborns, the majority of mothers' knowledge in the good category met the standard, 14 (38.9%) and the minority's knowledge in the good and sufficient categories did not meet the standards, 3 (8.3%) The results of bivariate analysis using chi square obtained a value of p=0.023 (p>0.05). To improve midwifery services, it is recommended to increase mothers' knowledge through education about the importance of umbilical cord care